Titik Temu Ideologi Pendidikan Islam Konservatif dan Liberal - Rofiqotul Aini (Edukasia Islamika, 2017)
The development of education has revealed a lot of educational ideology which makes some education practitioners often change the curriculum and educational model. This reality, then, leads to the changes of Indonesian curriculum which consequently shows that Indonesian education ideology is inconsistent. Actually, without following the western education ideology, Muslim practitioners in Indonesia should be able to maintain and use their own education ideology, namely Islamic education ideology. Because of its universal and transcendental characteristic, Islamic education ideology can give the newest and up-to-date format for the era development. This paper describes the concept of each ideology and their meeting points. The research method used in this study is library research method, and the data was analyzed by using content analysis method. The reserch result shows that the meeting points of those ideologies are divided into four concepts. First, the objective of education is to optimize the human resource. Second, the concept of human being is that human is the most noble and creative creation. Third, the education curriculum should be applicable. Forth, it is better to use guidance and counseling method in guiding students in solving their problems.